Analisis Peramalan Penjualan Produk Dalam Optimalisasi Stok Pada UMKM - Widiyanti; Raden Firyal F Camila; Wiji Safitri; Nur Hidayati (Apik Cahaya Ilmu, 2024)
Forecasting is a method of predicting sales in the next period. Satay as Indonesia's favorite food should use fresh ingredients because it affects the taste. The mismatch between the amount of production and demand results in the company experiencing excess stock. Thus, this study aims to determine and forecast the sales of Warung Sate Sido Stop by Pak Min Solo. This study used a quantitative approach, where the data collection method was carried out by means of interview and observation techniques. The population and sample in this study used sales data for the period January to September 2023, and the sampling technique for this study used non-probability sampling techniques, namely judgment sampling. The data analysis technique used is forecasting with moving average and exponential smoothing methods. Tools used in processing data using Ms.Excel through the stages of data collection, calculation, selection and application of appropriate forecasting. The results of forecasting analysis show that the exponential smoothing method with α = 0.9 is better to use because this forecasting method has the smallest overall error rate value of 8.90%. Thus, these MSMEs should follow the calculation of the exponential smoothing forecasting method with α = 0.9 because they are able to forecast and determine the optimal amount of production so that satay is always with fresh raw materials.